2022
DOI: 10.3390/ijms23063069
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Silica Nanoparticles Targeting Mitochondria: Trafficking in Myeloid Cells and Application as Doxorubicin Delivery System in Breast Cancer Cells

Abstract: Fluorescent silica nanoparticles (SiNPs) appear to be a promising imaging platform, showing a specific subcellular localization. In the present study, we first investigated their preferential mitochondrial targeting in myeloid cells, by flow cytometry, confocal microscopy and TEM on both cells and isolated mitochondria, to acquire knowledge in imaging combined with therapeutic applications. Then, we conjugated SiNPs to one of the most used anticancer drugs, doxorubicin (DOX). As an anticancer agent, DOX has hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our experience is specifically related to fluorescent silica nanoparticles (SiNPs), which appear to be a promising imaging platform and show a specific subcellular localization that is mainly at the mitochondrial level. We conjugated SiNPs to one of the most commonly used anticancer drugs, doxorubicin, and we tested these functionalized SiNPs (DOX-NPs) on the breast cancer cell line MCF-7 [ 77 ]. Generally, carrier nanoparticles (NPs) reveal a poor penetration capacity and an inadequate balance between drug retention in the bloodstream and drug release at the specific pathologic body districts [ 78 ].…”
Section: Extracellular Vesicles: An Overview Of Their Origin and Comp...mentioning
confidence: 99%
“…Our experience is specifically related to fluorescent silica nanoparticles (SiNPs), which appear to be a promising imaging platform and show a specific subcellular localization that is mainly at the mitochondrial level. We conjugated SiNPs to one of the most commonly used anticancer drugs, doxorubicin, and we tested these functionalized SiNPs (DOX-NPs) on the breast cancer cell line MCF-7 [ 77 ]. Generally, carrier nanoparticles (NPs) reveal a poor penetration capacity and an inadequate balance between drug retention in the bloodstream and drug release at the specific pathologic body districts [ 78 ].…”
Section: Extracellular Vesicles: An Overview Of Their Origin and Comp...mentioning
confidence: 99%
“…In this regard, fluorescent silica nanoparticles (SiNPs) appear to be a promising imaging platform, as they show intramitochondrial colocalization in biological cell models and can be used as efficient drug delivery systems when conjugated to a therapeutic molecule. Sola et al [9] performed an experimental study aimed to characterize the intracellular targeting of SiNPs in myeloid cell lines and the cytotoxicity and cellular effects of doxorubicin-conjugated SiNPs (DOX-NPs) on the breast cancer line MCF-7. Their results indicated that DOX-NPs are endocytosed and co-localize with lysosomes, inducing a cell cycle arrest and promoting apoptosis.…”
mentioning
confidence: 99%